Peran Pemerintah dalam Pelaksanaan Ibadah Haji di Aceh - Eka Prasetya Yunus; Alindawati Dako; Faisal Faisal; Roni Mohamad (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This article focuses on the government's role in regulating and supporting the implementation of the Hajj pilgrimage in Aceh. Its background encompasses Aceh as one of the regions in Indonesia with high participation rates in the Hajj pilgrimage, yet facing challenges in adequate management and regulation. The research problem identifies various aspects, including government regulations concerning quotas, facilities, and the protection of Hajj pilgrims. Through policy analysis and empirical data, it was found that the Aceh government plays a crucial role in efficiently and safely organizing the Hajj pilgrimage. The conclusion emphasizes the government's vital role in organizing, overseeing, and providing necessary facilities for Hajj pilgrims. The novelty of this academic work lies in emphasizing the specific role of the regional government in the context of implementing the Hajj pilgrimage in Aceh, along with an analysis of successes and obstacles faced. This study offers profound insights into the importance of coordination between the central and regional governments in organizing the Hajj pilgrimage, highlighting efforts needed to improve policies and related infrastructure to enhance the Hajj pilgrims' experiences in the future.